Verification of IDL Arcitecture Performance for Larger Datasets - Majerík, Filip; Borkovcová, Monika (IEEE (Institute of Electrical and Electronics Engineers), 2024)
Due to the ever increasing popularity of Object Relational Mapping (ORM) frameworks, the Intelligent Data Layer (IDL) architecture was compiled by the authors as part of an earlier publication, Design of Data Access Architecture Using ORM Framework. This architecture allows to implement ORM frameworks with prediction of the required data. Given the size of datasets that can be managed in database systems, it was necessary to verify that this architecture is robust enough to handle similar problems. In the context of this paper, we focus on examining the performance of our defined architecture with larger datasets, which should help us determine whether such an architecture is suitable for common use. Along with the performance verification for larger datasets, performance tests were performed in case the database does not contain indexes for foreign keys.
Ověření výkonu architektury IDL pro větší soubory dat
Keywords: technological innovation; memory management; indexes; optimization; technologické inovace; správa paměti; indexy; optimalizace